Phytic acid modified zirconium oxide porous carbon composite material, preparation method thereof and application of phytic acid modified zirconium oxide porous carbon composite material in indium (III) adsorption

By introducing phytic acid into the porous carbon zirconia composite material, an efficient indium adsorbent was prepared, which solved the problems of low adsorption capacity and slow kinetics of existing adsorbents, and achieved efficient and fast indium (III) adsorption and excellent regeneration performance.

CN119455900AActive Publication Date: 2025-02-18LIAONING UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411607592.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing indium adsorbent has low adsorption capacity and slow adsorption kinetics, making it difficult to efficiently recover indium.

Method used

NH2-UiO-66 was synthesized by hydrothermal method, pyrolyzed to prepare zirconia porous carbon composite material, and phytic acid was introduced by hydrothermal method to prepare phytic acid-modified zirconia porous carbon composite material to improve the indium (III) Adsorption capacity.

Benefits of technology

It has achieved efficient adsorption of indium (III). When the pH is 2.5, the adsorption amount can reach 146.92 mg·g-1. It has excellent kinetic performance. It can achieve equilibrium in only 3 hours, and has excellent selectivity and regeneration performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130030230000041
    Figure BDA0005130030230000041
  • Figure HDA0005130030240000011
    Figure HDA0005130030240000011
  • Figure HDA0005130030240000012
    Figure HDA0005130030240000012
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of composite materials and adsorption of scattered metal indium (III), and particularly relates to a phytic acid modified zirconium oxide porous carbon composite material, a preparation method of the phytic acid modified zirconium oxide porous carbon composite material and application of the phytic acid modified zirconium oxide porous carbon composite material to adsorption of indium (III). The composite material xPA-ZrMC is prepared by modifying zirconium oxide porous carbon with a phytic acid solution, wherein x is the amount of added phytic acid. The phytic acid modified zirconium oxide porous carbon composite material prepared by the preparation method disclosed by the invention shows excellent adsorption performance on indium (III), and the saturated adsorption capacity reaches 146.92 mg.g <-1 >. The composite material prepared by the invention is simple to operate, has the characteristics of high adsorption efficiency, good adsorption effect and the like, and can be used for recycling indium (III) in actual ore liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of composite materials and adsorption of scattered metal indium (III), and specifically relates to a plant acid-modified zirconium oxide porous carbon composite material and a preparation method thereof and application in adsorbing indium (III). Background Art

[0002] Indium is widely used in optoelectronics, military industry, aviation, national defense and other fields due to its unique properties. However, the content of indium in the earth's crust is less than one part per million, and the global proven indium reserves are only 32,000-35,000 tons. At present, no independent deposits of indium have been found. Indium is usually associated with non-ferrous metal sulfide ores. Adsorbents are commonly used in industry to absorb and recover indium from sulfide ore liquid, but the recovery rate is only 50%. Therefore, studying an efficient and economical adsorbent for recovering indium has become the focus of current research.

[0003] The adsorption method is to selectively adsorb a certain element in the sample through an adsorbent in order to achieve the purpose of separating and enriching a certain product. Phosphate-based adsorbents have excellent adsorption performance for indium. The mechanism is that the OH bond on the phosphate group is ionized, and the empty orbital of indium combines with the lone pair of electrons on the O atom through electrostatic attraction, resulting in ion exchange, thereby adsorbing indium in the sample.

[0004] There are many types of adsorbents. Carbon materials are widely used in adsorbent matrices due to their high chemical stability and porosity. However, carbon materials lack specific adsorption sites and have disordered porous structures. Carbon materials synthesized using metal organic framework materials (MOFs) as precursors have the advantages of structural adjustability, porosity, and high specific surface area. Therefore, the present invention uses MOFs-derived carbon materials as a matrix to synthesize a phytic acid-modified ordered porous carbon material with abundant active sites, so as to improve the adsorption capacity of the adsorbent for indium (III). Summary of the invention

[0005] In order to solve the problems of low adsorption capacity and slow adsorption kinetics of indium adsorbent, the present invention develops and designs a phytic acid-modified zirconium oxide porous carbon composite material adsorbent. Firstly, 2-aminoterephthalic acid is used as a ligand, and NH 2 -UiO-66, NH 2 After pyrolysis of -UiO-66, a zirconium oxide porous carbon composite material (ZrMC) is obtained. Then, zirconium oxide is used as a modification site, and phytic acid is introduced into the zirconium oxide porous carbon composite material by a hydrothermal method. Zirconium oxide has a strong affinity for phytic acid, and the abundant phosphate groups in phytic acid provide a large number of active sites for the adsorption of indium (III). The present invention is easy to operate, has a good adsorption effect, and has a high practical value.

[0006] The present invention is achieved through the following technical scheme: a phytic acid-modified zirconium oxide porous carbon composite material, which is a composite material xPA-ZrMC prepared by modifying ZrMC with a phytic acid solution, wherein x is the amount of added phytic acid.

[0007] The method for preparing the above-mentioned acid-modified zirconium oxide porous carbon composite material comprises the following steps:

[0008] 1) Dissolve 2-aminoterephthalic acid in N,N-dimethylformamide, then add zirconium chloride and stir; transfer the stirred solution to a hydrothermal reactor for hydrothermal reaction, wash the precipitate and dry it after the reaction to obtain NH 2 -UiO-66.

[0009] 2) Weigh the NH prepared in step 1) 2 -UiO-66 powder was pyrolyzed to obtain zirconium oxide porous carbon composite material (ZrMC).

[0010] 3) adding the phytic acid solution to the ZrMC prepared in step 2) and mixing them evenly by ultrasonication; transferring the mixture to a hydrothermal reactor for hydrothermal reaction after ultrasonication, washing the precipitate after the reaction and drying it to obtain a phytic acid-modified zirconium oxide porous carbon composite material (xPA-ZrMC).

[0011] The above-mentioned method for preparing a phytic acid-modified zirconium oxide porous carbon composite material comprises the following steps: in step 1), the molar ratio of 2-aminoterephthalic acid to zirconium chloride is 2:1.

[0012] In the above-mentioned method for preparing the acid-modified zirconium oxide porous carbon composite material, in step 1), the hydrothermal reaction temperature is 100-150° C., and the reaction time is 12-36 hours.

[0013] In the above-mentioned method for preparing a phytic acid-modified zirconium oxide porous carbon composite material, in step 2), the pyrolysis temperature is 800-1200°C and the rate is 5°C·min -1 , time is 1-6h.

[0014] In the above-mentioned method for preparing the acid-modified zirconium oxide porous carbon composite material, in step 3), the hydrothermal reaction temperature is 100-140° C., and the reaction time is 8-16 hours.

[0015] In the above-mentioned method for preparing a phytic acid-modified zirconium oxide porous carbon composite material, in step 3), the amount of phytic acid:ZrMC is 1-5mL:0.1g.

[0016] The above-mentioned phytic acid-modified zirconium oxide porous carbon composite material is used as an adsorbent in the recovery of indium (III).

[0017] The above application method is as follows: add the acid-modified zirconium oxide porous carbon composite material according to claim 1 to a solution containing indium (III), and shake at 30-50° C. for 24 hours.

[0018] In the above application, the pH of the solution containing indium (III) is 1-4, and the concentration of indium (III) is 20 mg·L - 1. According to the solid-liquid ratio, phytic acid-modified zirconium oxide porous carbon composite material: solution containing indium (III) = 1g:1L.

[0019] The beneficial effects of the present invention are:

[0020] 1. The synthesis method of the present invention is simple. The present invention first prepares NH by a hydrothermal method. 2 -UiO-66 precursor, which was then pyrolyzed to prepare a zirconia porous carbon composite material, and then phytic acid was in situ loaded into the zirconia porous carbon by a hydrothermal method to obtain a phytic acid-modified zirconia porous carbon composite material (xPA-ZrMC).

[0021] 2. Indium (III) reaches the surface of the adsorbent through electrostatic attraction, and the phosphate groups on the surface of the adsorbent combine with indium (III). The lone pair of electrons provided by the O atom on the PO single bond on the phosphate group combines with the empty orbital on indium (III), successfully adsorbing indium (III).

[0022] 3. The adsorbent xPA-ZrMC prepared by the present invention has excellent adsorption performance. When pH = 2.5, the adsorption effect on indium (III) is the best, and the adsorption amount can reach 146.92 mg g -1 , exceeding most reported adsorbents.

[0023] 4. In the present invention, the adsorbent xPA-ZrMC has remarkable kinetic properties and can reach equilibrium in only 3 hours. It also has superior selectivity and excellent regeneration performance for capturing indium (III). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 (a) is NH 2 -Scanning electron microscope (SEM) image of UiO-66, (b) is the SEM image of ZrMC.

[0025] Figure 2 Elemental mapping diagram of 4PA-ZrMC prepared in Example 5, wherein (a) is the elemental mapping diagram of O, (b) is the elemental mapping diagram of C, (c) is the elemental mapping diagram of P, and (d) is the elemental mapping diagram of Zr.

[0026] Figure 3 Infrared spectra of 4PA-ZrMC and ZrMC prepared in Example 5 and Example 7.

[0027] Figure 4 (a) shows the adsorption efficiency of indium (III) by PA-ZrMC and ZrMC prepared in Example 2 and Example 7 at different acidities; (b) shows the adsorption capacity of indium (III) by xPA-ZrMC prepared in Example 1 at different acidities.

[0028] Figure 5 (a) is the adsorption isotherm of indium (III) by PA-ZrMC prepared in Example 2; (b) is the adsorption isotherm of indium (III) by 2PA-ZrMC prepared in Example 3; (c) is the adsorption isotherm of indium (III) by 3PA-ZrMC prepared in Example 4; (d) is the adsorption isotherm of indium (III) by 4PA-ZrMC prepared in Example 5; (e) is the adsorption isotherm of indium (III) by 5PA-ZrMC prepared in Example 6; (f) is the adsorption isotherm of indium (III) by ZrMC prepared in Example 7.

[0029] Figure 6 This is the dynamic adsorption breakthrough curve of indium (III) by 4PA-ZrMC prepared in Example 5.

[0030] Figure 7 (a) is the elution rate of indium (III) by 4PA-ZrMC prepared in Example 5 under different eluents; Figure 7 (b) The cyclic regeneration performance of 4PA-ZrMC prepared in Example 5 for the adsorption of indium (III). DETAILED DESCRIPTION

[0031] Example 1 Preparation of phytic acid modified zirconium oxide porous carbon composite material (xPA-ZrMC)

[0032] (I) Preparation method

[0033] 1) Accurately weigh 1.661 g of 2-aminoterephthalic acid and dissolve it in 50 mL of N,N-dimethylformamide, then add 1.165 g of zirconium chloride and stir continuously for 40 min. Transfer the solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor and heat at 120 °C for 24 h. After the reaction is completed, wash the precipitate three times with methanol and N,N-dimethylformamide respectively, and finally dry it in a vacuum oven at 80 °C for 6 h to obtain NH 2 -UiO-66.

[0034] 2) Weigh 100 mg NH 2 -UiO-66 was pyrolyzed at 800 °C for 2 h to obtain the ZrMC composite material.

[0035] 3) Weigh 0.1 g of ZrMC prepared in 2) into a beaker, add deionized water, then add different volumes (x mL) of 70% phytic acid solution, ultrasonicate for 30 min, then transfer the mixed solution to a 25 mL polytetrafluoroethylene-lined hydrothermal reactor and heat at 120°C for 12 h. After the reaction is completed, wash the precipitate with deionized water until it is neutral, and finally dry it in a vacuum oven at 50°C for 4 h to obtain the xPA-ZrMC composite material.

[0036] Example 2 Preparation of phytic acid modified zirconium oxide porous carbon composite material (PA-ZrMC)

[0037] According to steps 1) to 3) in Example 1, the volume of the phytic acid solution in step 3) is controlled to be 1 mL, and a phytic acid-modified zirconium oxide porous carbon composite material is prepared to obtain PA-ZrMC.

[0038] Example 3 Preparation of phytic acid modified zirconium oxide porous carbon composite material (2PA-ZrMC)

[0039] According to steps 1) to 3) in Example 1, the volume of the phytic acid solution in step 3) is controlled to be 2 mL, and a phytic acid-modified zirconium oxide porous carbon composite material is prepared to obtain 2PA-ZrMC.

[0040] Example 4 Preparation of phytic acid modified zirconium oxide porous carbon composite material (3PA-ZrMC)

[0041] According to steps 1) to 3) in Example 1, the volume of the phytic acid solution in step 3) is controlled to be 3 mL, and a phytic acid-modified zirconium oxide porous carbon composite material is prepared to obtain 3PA-ZrMC.

[0042] Example 5 Preparation of phytic acid modified zirconium oxide porous carbon composite material (4PA-ZrMC)

[0043] According to steps 1) to 3) in Example 1, the volume of the phytic acid solution in step 3) is controlled to be 4 mL, and a phytic acid-modified zirconium oxide porous carbon composite material is prepared to obtain 4PA-ZrMC.

[0044] Example 6 Preparation of phytic acid modified zirconium oxide porous carbon composite material (5PA-ZrMC)

[0045] According to steps 1) to 3) in Example 1, the volume of the phytic acid solution in step 3) is controlled to be 5 mL, and a phytic acid-modified zirconium oxide porous carbon composite material is prepared to obtain 5PA-ZrMC.

[0046] Example 7 Preparation of zirconium oxide porous carbon composite material (ZrMC)

[0047] According to step 2) in Example 1, a zirconium oxide porous carbon composite material is prepared to obtain ZrMC.

[0048] Example 8 Characterization of Phytic Acid Modified Zirconia Porous Carbon Composite Material (xPA-ZrMC)

[0049] The products prepared in Example 1, Example 2, Example 5 and Example 7 were subjected to scanning electron microscopy, energy dispersive X-ray spectroscopy, infrared spectroscopy and N 2 Adsorption analysis characterization, such as Figure 1 , Figure 2 , Figure 3 As shown in Table 1. Figure 1 It can be seen that the zirconia porous carbon composite material presents a sphere with a rough surface and the nanometer size is smaller than that of NH 2 -UiO-66 nanoparticles; Figure 2 The elemental mappings in (a)-(d) show the uniform dispersion of C, O, P, and Zr elements. Figure 3 This indicates that phosphate groups appeared in ZrMC after phytic acid modification, with a peak at 1160 cm -1 and 974cm -1 The results are attributed to the stretching vibrations of the P=O double bond and the PO single bond of the phosphate group, respectively. The abundant phosphate groups provide active sites for the adsorption of In(III).

[0050] Table 1 Pore structure parameters of adsorbent 4PA-ZrMC prepared in Example 5

[0051]

[0052] Example 9 Adsorption of Indium (III) by Adsorbent xPA-ZrMC at Different Acidities

[0053] Method: Take the concentration of 20mg·L -1 The indium (III) solution was adjusted to pH 1-4, and PA-ZrMC and ZrMC prepared in Example 2 and Example 7 were added at a solid-liquid ratio of 1:1, and the adsorption rate was calculated.

[0054] The results are as follows Figure 4 As shown in (a), the adsorption rate increases significantly with the increase of solution pH. When the pH is 2.5, the adsorption rate of PA-ZrMC for indium (III) is the largest, and remains stable as the pH further increases. The adsorption group is easily protonated when the pH is low, and the hydrogen ions and indium (III) compete for the adsorption site, reducing the adsorption performance of indium (III). In actual situations, the indium (III) solution is acidic, so the optimal pH value for adsorbing indium (III) is 2.5.

[0055] Example 10 Effect of phytic acid addition on the adsorption of indium (III) by xPA-ZrMC

[0056] Method: Weigh 5 mg of xPA-ZrMC prepared in Example 2, Example 3, Example 4, Example 5, and Example 6 with different volumes of phytic acid added, and add them to 10 mL of 20 mg·L - 1 indium (III) solution, the pH of the solution was adjusted to 1-4, and the mixture was shaken at 30°C for full adsorption.

[0057] The results are as follows Figure 4 As shown in (b), the adsorption rate of indium (III) by xPA-ZrMC gradually increases with the increase of phytic acid addition, and the adsorption rate tends to be stable when the phytic acid addition amount is 4 mL.

[0058] Example 11 Adsorption experiment of indium (III) on phytic acid modified zirconium oxide porous carbon composite material xPA-ZrMC

[0059] Method for adsorbing indium (III): prepare indium (III) solutions of different concentrations, adjust the pH to 2.5, weigh several 5 mg portions of different adsorbents, mix them in a solid-liquid ratio of 1:1, shake at 30°C for sufficient adsorption, then filter, and determine the concentration of indium (III) in the filtrate by atomic absorption spectrometry.

[0060] like Figure 5 As shown in the figure, three adsorption isotherm models were used to fit the data (Langmuir, Freundlich and Temkin), and it was found that the adsorption process of indium (Ⅲ) by ZrMC, PA-ZrMC, 2PA-ZrMC, 3PA-ZrMC, 4PA-ZrMC and 5PA-ZrMC was more consistent with the Langmuir model, indicating a monolayer adsorption process. After fitting, the saturated adsorption capacities of indium (Ⅲ) by ZrMC, PA-ZrMC, 2PA-ZrMC, 3PA-ZrMC, 4PA-ZrMC and 5PA-ZrMC were 27.53, 80.66, 106.87, 130.51, 143.13 and 146.92 mg·g, respectively. -1 .

[0061] Example 12 Dynamic adsorption experiment of indium (III) by adsorbent 4PA-ZrMC

[0062] Dynamic adsorption method of indium (III): first add an appropriate amount of quartz sand to the adsorption column, then add a certain amount of adsorbent 4PA-ZrMC to the column; then add cotton and quartz sand in sequence, and the column filling process is completed. Then first pass a certain amount of water to ensure that the adsorption column can flow normally, and then pass the metal ion solution to be tested, and adjust the flow rate to 6.5mL·h -1 , collect the effluent with a receiver and measure the indium (III) concentration in the effluent.

[0063] from Figure 6The dynamic adsorption breakthrough curve shows that 4PA-ZrMC can efficiently adsorb 225 mL of liquid, indicating that it has the potential to efficiently recover indium (III) from indium-rich zinc ore tailings.

[0064] Example 13 Cycle-elution adsorption performance of adsorbent 4PA-ZrMC for indium (III)

[0065] The method of cyclic-elution of indium (III): accurately weigh 5 mg of 4PA-ZrMC adsorbent on an analytical balance into a small oscillating bottle, add indium (III) at a solid-liquid ratio of 1:1, mix well, place the small bottle in a constant temperature oscillating box for a period of time, filter, and retain the filtrate for testing; then dry the filtered adsorbent material, rinse, and continue to add different eluents at a solid-liquid ratio of 1:1 for elution, shake and filter again under the same conditions, collect the filtrate, and use an atomic absorption spectrometer to determine the concentration. Finally, select the eluent with the highest elution rate for the next cyclic-elution experiment.

[0066] Figure 7 (a) shows that nitric acid, sulfuric acid, and hydrochloric acid were used for the elution experiment. Nitric acid had the best elution efficiency. When the concentration of nitric acid was 2 mol·L -1 When the elution efficiency is above 90%, Figure 7 (b) It can be seen that the adsorption rate of 4PA-ZrMC composite material can still be maintained above 85% after 4 repeated use cycles.

Claims

1. A phytic acid-modified zirconium oxide porous carbon composite material, characterized in that: The composite material xPA-ZrMC is prepared by modifying ZrMC with a phytic acid solution, wherein x is the amount of phytic acid added.

2. The method for preparing the acid-modified zirconium oxide porous carbon composite material according to claim 1, characterized in that: The steps include: 1) dissolving 2-aminoterephthalic acid in N,N-dimethylformamide, then adding zirconium chloride and stirring; transferring the stirred solution to a hydrothermal reactor for hydrothermal reaction, washing the precipitate after the reaction and drying it to obtain NH2-UiO-66; 2) Weighing the NH2-UiO-66 powder prepared in step 1) and pyrolyzing it to obtain a zirconium oxide porous carbon composite material ZrMC; 3) adding the phytic acid solution to the ZrMC prepared in step 2) and mixing them evenly by ultrasonication; transferring the mixture to a hydrothermal reactor for hydrothermal reaction after ultrasonication, washing the precipitate after the reaction and drying it to obtain a phytic acid-modified zirconium oxide porous carbon composite material xPA-ZrMC.

3. The method for preparing a plant acid-modified zirconium oxide porous carbon composite material according to claim 2, characterized in that: In step 1), the molar ratio of 2-aminoterephthalic acid to zirconium chloride is 2:

1.

4. The method for preparing a plant acid-modified zirconium oxide porous carbon composite material according to claim 2, characterized in that: In step 1), the hydrothermal reaction temperature is 100-150° C. and the reaction time is 12-36 h.

5. The method for preparing a plant acid-modified zirconium oxide porous carbon composite material according to claim 2, characterized in that: In step 2), the pyrolysis temperature is 800-1000°C and the heating rate is 5°C·min -1 , time is 1-6h.

6. The method for preparing a plant acid-modified zirconium oxide porous carbon composite material according to claim 2, characterized in that: In step 3), the hydrothermal reaction temperature is 100-140° C. and the reaction time is 8-16 h.

7. The method for preparing a plant acid-modified zirconium oxide porous carbon composite material according to claim 2, characterized in that: In step 3), the amount of phytic acid:ZrMC is 1-5mL:0.1g.

8. Use of the acid-modified zirconium oxide porous carbon composite material according to claim 1 as an adsorbent in the recovery of indium (III).

9. The use according to claim 8, characterized in that: The method is as follows: adding the phytic acid-modified zirconium oxide porous carbon composite material according to claim 1 to a solution containing indium (III), and shaking at 30-50° C. for 24 hours.

10. The use according to claim 8, characterized in that: The pH of the solution containing indium (III) is 1-4, and the concentration of indium (III) is 20 mg·L - 1. According to the solid-liquid ratio, phytic acid-modified zirconium oxide porous carbon composite material: solution containing indium (III) = 1g:1L.

Citation Information

Patent Citations

  • Carbon material adopting Zr-MOFs composite material as template, preparation method and application of carbon material

    CN106910638A

  • Preparation method of impregnating resin for adsorbing scattered metal indium (III)

    CN109158091A

  • Black mesoporous carbon loaded ZrO2 nanoparticles and preparation method and application thereof

    CN111573727A

  • Preparation method of phosphate functionalized carbon sphere material and application of phosphate functionalized carbon sphere material as adsorbent in In (III) ion adsorption

    CN116943607A